Pandita Dalam Teks Lontar Tutur Gong Besi - Mery Ambarnuari; Hari Harsananda (Kamaya: Jurnal Ilmu Agama, 2023)
The institutionalization of Hindu religious teachings, especially the Siwaistic understanding, is inextricably linked to the duty of the clergy,who in this case are certainly more dominated by Pandita/Sulinggih. Pandita means learned, scholar, teacher, teacher, especially one who studies and is an expert in the spiritual field; wise men, saints, brahmanas, wiku, rsi, priests. Descriptive qualitative method used in this study. The purpose of this research is to ascertain the teachings of the priesthood contained in the lontar text of Gong Besi. The lontar text of Tutur Gong Besi states that a Pandita is said to be perfect if he knows the nature of life as a human being, is able to distinguish worldly things (sakala) which causes attachment to maya. Additionally to understanding the true things that are actually the goal of human life (things related to abstraction). Thus, a Pandita must always purify himself and master religious teachings so that he can appropriately do his tasks as a guide for the people.